2000
DOI: 10.1063/1.1288791
|View full text |Cite
|
Sign up to set email alerts
|

The direct production of CO(v=1–9) in the reaction of O(3P) with the ethyl radical

Abstract: A new product channel that yields vibrationally excited in the reaction of the ethyl radical with O( 3 P) is experimentally observed by time-resolved Fourier transform infrared emission spectroscopy. The branching ratios for the different vibrational states are estimated to be 0.21Ϯ0.06, 0.27Ϯ0.03, 0.14Ϯ0.02, 0.08Ϯ0.02, 0.07Ϯ0.02, 0.07Ϯ0.02, 0.06Ϯ0.02, 0.05Ϯ0.02, and 0.05Ϯ0.02 for vϭ1 -9, respectively. Previously, only the CH 3 ϩH 2 CO, CH 3 CHOϩH, and C 2 H 4 ϩOH channels were known. Kinetics tests are provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 32 publications
(41 reference statements)
1
27
0
Order By: Relevance
“…The internal energy of the ethoxy radical formed in these reactions was peaked at roughly 4.0, 2.5, and 1.5 eV, respectively. CH 3 + CH 2 O formation was favored when O 3 and NO 3 were used, and the resulting internal energy of the ethoxy radical was lower; when O was used, the H + CH 3 CHO channel was favored. OH + C 2 H 4 was also seen in this study when ethyl radical reacted with O and O 3 , but RRKM calculations implied that this channel was due to direct abstraction of a H atom from the ethyl radical and did not involve ethoxy as an intermediate.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The internal energy of the ethoxy radical formed in these reactions was peaked at roughly 4.0, 2.5, and 1.5 eV, respectively. CH 3 + CH 2 O formation was favored when O 3 and NO 3 were used, and the resulting internal energy of the ethoxy radical was lower; when O was used, the H + CH 3 CHO channel was favored. OH + C 2 H 4 was also seen in this study when ethyl radical reacted with O and O 3 , but RRKM calculations implied that this channel was due to direct abstraction of a H atom from the ethyl radical and did not involve ethoxy as an intermediate.…”
Section: Introductionmentioning
confidence: 99%
“…2,18 The reaction of O( 3 P) with ethyl radical, which can lead to the formation of the ethoxy radical with a great deal of excess energy, has been the subject of several experimental studies. [2][3][4]18,19 The fragmentation of chemically activated ethoxy radical formed in the reactions of ethyl radical with O, O 3 , and NO 3 was compared, 2 and it was found that both CH 3 + CH 2 O and H + CH 3 CHO were formed in all cases. The internal energy of the ethoxy radical formed in these reactions was peaked at roughly 4.0, 2.5, and 1.5 eV, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations